2017
DOI: 10.1111/ijcs.12357
|View full text |Cite
|
Sign up to set email alerts
|

Knowing how to use and understand recipes: What arithmetical understanding is needed when students with mild intellectual disabilities use recipes in practical cooking lessons in Home Economics?

Abstract: The aim of this study was to explore what arithmetical understanding is needed when students with mild intellectual disabilities use recipes during practical cooking lessons in Home Economics.The settings were compulsory schools in Sweden attended by students with intellectual disabilities. Sixteen lessons in Home Economics during which cooking took place were observed. In total, 37 students and three teachers participated. All students had a mild intellectual disability. Their ages varied, but most were betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Inte minst att läsa och skapa recept som baserades på erfarenheter i skolköket gav eleverna en särskild kompetens samtidigt som de övade sina färdigheter i svenska. Även andra kunskaper och färdigheter är nödvändiga för att förstå och kunna komponera recept, vilket uppmärksammats i studier om undervisningen i hem-och konsumentkunskap där forskarna argumenterar för användningen av begreppet "recipe literacy" (Brunosson et al, 2014;Granberg et al, 2017).…”
Section: Sammanfattande Diskussionunclassified
“…Inte minst att läsa och skapa recept som baserades på erfarenheter i skolköket gav eleverna en särskild kompetens samtidigt som de övade sina färdigheter i svenska. Även andra kunskaper och färdigheter är nödvändiga för att förstå och kunna komponera recept, vilket uppmärksammats i studier om undervisningen i hem-och konsumentkunskap där forskarna argumenterar för användningen av begreppet "recipe literacy" (Brunosson et al, 2014;Granberg et al, 2017).…”
Section: Sammanfattande Diskussionunclassified
“…I det ingick att lära sig språk kring matlagning, matlagningstekniker, vissa maträtter, att mäta och att följa recept. I en annan artikel observerade Granberg et al (2017a) matlagning efter recept inom hem-och konsumentkunskap för elever med IF. De fann att eleverna behövde lära sig aritmetiska kunskaper för att kunna följa recept, såsom nummer/tal, mängder och beräkningar.…”
Section: Kunskapsinnehålletunclassified
“…Brante & Brunosson [6]) have shown that students have difficulties in transferring subject-specific knowledge from other school subjects or real-life situations. The reasons for this are the lack of an ability to see the link between different pieces of school-learned knowledge, having an incorrect understanding of various concepts or not understanding the meaning of learning tasks [7], [8]. The Learning and Digitalisation in Home Economics Education (LEAD) project aimed to reveal possibilities how to integrate students' previous knowledge (from other school subjects as well as from students' out-of-school learning situations) and to build organised knowledge structures in home economics education.…”
Section: Introductionmentioning
confidence: 99%